Informal learning of popular music: gender monoglossia and heteroglossia. Issue 1 (14th March 2021) - Butler, Alison; Bylica, Kelly; Wright, Ruth
Abstract: This paper reports on a small-scale study in an elementary school in Southern Ontario, Canada. The study investigated relationships between students' perceptions and practices of gender in popular music education with particular attention given to communication, instruments and technology and development of freedoms and constraints. The findings present a more opaque picture than previous research, suggesting that students frequently transgress binary gendered patterns of practice and perception in this particular field. Gender monoglossia and heteroglossia provide a useful explanatory framework for analysis, indicating that further application of these concepts to issues in popular music education might be most fruitful.